EVALUATION AS AN INTEGRAL PART OF A SUMMER SCIENCE PROGRAM FOR TALENTED HIGH SCHOOL STUDENTS. - Charters Lyon, Margaret (Science Education, 1963)
The article reports the evaluation project performed during the summer science program for talented high school students of Livingston State College in Livingston, Alabama. The five-week summer program, sponsored by the National Science Foundation is created for 25 tenth and eleven grade students with scientific interest. The evaluation project was facilitated by one faculty supervisor, a number of student assistants and five science major college seniors who already completed their teacher education program. The preparation of a summary sheet which contains the test scores of each high school student was the first formal step of the evaluation project. A rating scale of scientific behavior was also prepared by college seniors. This scale contains anecdotal records of the student's scientific behavior during the laboratory periods of the summer program.